Heaven is for Real : A Little Boy's Astounding Story of His Trip to Heaven and Back - Burpo, Todd and Vincent, Lynn (Nashville, Tenn. Thomas Nelson, 2010)
With disarming innocence and the plainspoken boldness of a child, Colton tells of meeting long-departed family members. He describes Jesus, the angels, how "really, really big" God is, and how much God loves us. Retold by his father, but using Colton's uniquely simple words, Heaven Is for Real offers a glimpse of the world that awaits us.
Include Illustration
Keywords: Burpo, Colton, 1999- -- Heaven--Christianity -- Near-death experiences--Religious aspects--Christianity